1996
DOI: 10.1136/ard.55.5.311
|View full text |Cite
|
Sign up to set email alerts
|

B cell clonality in gastric lymphoid tissues of patients with Sjogren's syndrome.

Abstract: 1996; 55: 311-316)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
4

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 28 publications
1
16
0
4
Order By: Relevance
“…For example, Epstein Barr virus has been implicated in the genesis of gastric carcinoma [Pagano, 1999, Herrera-Goepfert et al, 1999; herpes simplex virus and human cytomegalovirus have been occasionally associated to gastritis [Nelson andCrippin 1997, Zucker et al, 1994]. Gastric biopsies of patients with Sjo Ègren's syndrome may harbour EBV and HHV-6 DNA [Ferraccioli et al, 1996]. These observations suggested the opportunity to examine gastritis specimens for the presence of HHV-7.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, Epstein Barr virus has been implicated in the genesis of gastric carcinoma [Pagano, 1999, Herrera-Goepfert et al, 1999; herpes simplex virus and human cytomegalovirus have been occasionally associated to gastritis [Nelson andCrippin 1997, Zucker et al, 1994]. Gastric biopsies of patients with Sjo Ègren's syndrome may harbour EBV and HHV-6 DNA [Ferraccioli et al, 1996]. These observations suggested the opportunity to examine gastritis specimens for the presence of HHV-7.…”
Section: Discussionmentioning
confidence: 95%
“…Also, eradication of H. pylori does not necessarily lead to relief of clinical symptoms [Talley et al, 1999]. Second, the presence of herpesvirus DNA, in particular Epstein Barr virus (EBV) and human herpesvirus 6 (HHV-6), was reported in, respectively, 10% and 14% of gastric tissues [Ferraccioli et al, 1996]. The presence of HHV-6 in the gastric mucosa suggested the opportunity to extend the analysis to HHV-7, which is related closely to HHV-6 [Berneman et al, 1992;Nicholas, 1996;Megaw et al, 1998] and more prevalent in the human population [Di Luca et al, 1995b].…”
Section: Introductionmentioning
confidence: 99%
“…These organs are normally devoid of organized lymphoid tissue and lymphoma. MALT lymphomas arise from these sites as a result of chronic inflammatory or autoimmune disorders, such as H. pylori-associated chronic gastritis, lymphoepithelial sialoadenitis, Sjögren syndrome and Hashimoto thyroiditis (8,9). The common karyotypic alterations that characterize MALT lymphoma include the trisomies of 3 and 18 (10,11) and the translocations t(11;18) (q21;q21) (12,13), t(1;14)(p22;q32) (14,15), t(14;18)(q32;q21) (10,16), and t(3;14)(p14.1;q32) (17,18), which commonly activate the NF-κB pathway.…”
Section: Introductionmentioning
confidence: 99%
“…8,9,12,13 Autoimmunity may contribute to gastric chronic inflammation and lymphoproliferation. 11,[14][15][16][17][18][19] In particular, studies on SS-related chronic gastritis and gastric low-grade B-cell NHL showed intragastric B-cell clonal expansion also in the absence of HP infection. 11,18,19 Furthermore, recent clinical and experimental results have linked the HCV to SS-like manifestations and acquisition of MALT.…”
mentioning
confidence: 99%
“…11,[14][15][16][17][18][19] In particular, studies on SS-related chronic gastritis and gastric low-grade B-cell NHL showed intragastric B-cell clonal expansion also in the absence of HP infection. 11,18,19 Furthermore, recent clinical and experimental results have linked the HCV to SS-like manifestations and acquisition of MALT. 2,[20][21][22] We herein report the gastric mucosa as a possible extrahepatic localization of HCV.…”
mentioning
confidence: 99%